Assessment of the efficacy and safety of fluticasone propionate and salmeterol delivered as a combination dry powder via a capsule-based inhaler and a multi-dose inhaler in patients with asthma. (December 2016) - Chan, Robert; Sousa, Ana R.; Mallett, Stephen; Hynds, Peter; Homayoun-Valiani, Farshid; Tabberer, Maggie; Mehta, Rashmi
Abstract: Background: In developing countries, there is a need for access to affordable inhaled respiratory medicines. This study tested the clinical non-inferiority of fluticasone propionate/salmeterol combination (FSC) 50/250 μg Rotacaps ® /Rotahaler ® compared with FSC 50/250 μg Diskus ® . Methods: A multi-centre, randomised, double-blind, double-dummy study evaluated 12 weeks, twice daily treatment of FSC 50/250 μg administered using Rotacaps/Rotahaler or Diskus inhaler in a crossover design in patients with asthma (pre-bronchodilator forced expiratory volume in 1 s (FEV1 ) 40%–85% of predicted, FEV1 reversibility ≥12%, prior stable dose with inhaled corticosteroid (ICS) or ICS/long acting beta-agonist). The primary efficacy endpoint, change from baseline in trough morning FEV1 at Day 85, was analysed using a model for repeated measures analysis. The pre-defined criterion for non-inferiority was the lower limit of the CI (0.025, one-sided significance level) for the treatment difference (Rotacaps/Rotahaler-Diskus) in least squares (LS) mean change from baseline, being greater than −125 mL. Secondary endpoints included serial FEV1 measurements, morning peak expiratory flow (PEF), rescue medication use, day- and night-time asthma symptoms, Asthma Control Test (ACT) scores, and serial cortisol measured over 12 h (area under the curve (AUC0-12 )). Results: Treatment with FSC 50/250 μg via Rotacaps/Rotahaler or Diskus resulted in a similar LS mean increase from baseline in trough FEV1 at Day 85 (231 mL and 203 mL respectively). The difference in the model-adjusted LS mean change was 28 mL (95% CI -24 mL, 80 mL), fulfilling the criterion for non-inferiority. Data for all secondary endpoints were similar for the two treatments, supporting the primary endpoint findings. Both treatments were well tolerated and demonstrated similar safety profiles. Conclusion: This study demonstrated the clinical non-inferiority of FSC 50/250 μg when administered using Rotacaps/Rotahaler compared with administration using Diskus in patients with asthma, and suggests there is no difference in the risk:benefit profile between the two FSC inhalers.